THE TRANSFORMATION OF ZAKAT LAW: An Analysis of Ijtihād Maqāṣidī in the Modernisation of Zakat Practices in Indonesia - Bashori, Akmal; mutho'am, Mutho'am; Arianti, Farida; Kumala, Irma Nur; Nurviani, Eka; Mukarromah, Firda Laily (Jurisdictie: Jurnal Hukum dan Syariah, 2024)
Zakat is not merely a category of normative worship but also an aspect of mu’āmalah characterized by its adaptability. This notion is evident in the efforts of the National Zakat Agency (BAZNAS) of Kendal District to modernize zakat law, going far beyond what is stipulated in classical naṣ and fiqh. The modernization of zakat law at BAZNAS Kendal, the main focus of this article, is explored through empirical juridical research using a philosophical re-actualization approach, extensive interpretive analysis, and the theory of maqāṣidi ijtihād. The study finds that modernization is apparent in initiatives to mandate zakat from corporations as zakatable entities, with allocations for distribution in forms such as creative consumptive zakat for installing clean water facilities, creative productive zakat in the form of microfinance, and zakat for community development. Methodologically, Baznas Kendal employs the principles of maqāṣid al-shariֿ’ah, evident in its efforts to link normative zakat teachings (naṣ) with various dynamics of modern life (al-wāqi’) and considerations of social welfare as the essence of shari’a presence. Therefore, this study contributes to the reconstruction of pre-modern zakat law formulations whose conceptualization is no longer visible in the modern era into something more contextually meaningful, and it deepens the understanding of the conceptual framework for the modernization of zakat law that adheres to maqāṣid al-shariֿֿ’ah. Zakat bukan saja katagori ibadah kenormatifan yang given, melainkan juga mu’amalah dengan karakter adaptability (keberubahan). Anggapan ini terlihat dalam upaya Badan Amil Zakat Nasional (Baznas) Kabupaten Kendal memodernisasi hukum zakat jauh melampaui apa yang tertertuang dalam naṣ maupun fiqh klasik. Modernisasi hukum zakat di BAZNAS Kab. Kendal sebagai fokus utama dalam artikel ini menggunakan jenis penelitian yuridis empiris dengan pendekatan reaktualisasi filosofis dan analisis interpretatif ekstensif, dan teori ijtihād maqāṣidī. Penelitian ini menemukan bahwa modernisasi hukum terlihat pada upayanya mewajibkan perusahaan sebagai objek yang dikenai zakat, sementara alokasi distribusinya dalam bentuk: zakat konsumtif kreatif berupa pemasangan saluran air bersih, dan produktif kreatif berupa zakat micro finance, serta zakat community development. Secara metodologis Baznas Kendal menggunakan dalil maqāṣid al-shari’a, hal ini terlihat pada upayanya mengaitkan antara ajaran normatif zakat (naṣ) dengan berbagai faktor dinamika kehidupan modern (al-wāqi’), serta pertimbangan kemaslatan sosial sebagai intisari kehadiran shari’a. Dengan demikian penelitian ini berkontribusi merekonstruksi formulasi hukum zakat pramodern yang konseptualisasinya tidak lagi visible di masa modern menjadi lebih memberi makna aplikasi kontekstualnya, serta memperdalam pemahaman kerangka konsepsional modernisasi hukum zakat berbasis maqāṣid al-shariֿֿ’ah.